2010
DOI: 10.1111/j.1750-3841.2010.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tomatillo and Tomato Volatile Compounds in the Headspace by Selected Ion Flow Tube Mass Spectrometry (SIFT‐MS)

Abstract: The concentration of 31 volatiles were measured in the headspace of tomatillos using selected ion flow tube-mass spectrometry (SIFT-MS), and were compared with those in vine-ripened tomato, roma tomato, cherry tomato, and grape tomato. None of the volatiles were higher in the headspace of tomatillos than of tomatoes. Compounds (E)-2-octenal, (E)-2-pentenal, 2-isobutylthiazole, 6-methyl-5-hepten-2-one, and phenylacetaldehyde were significantly lower in tomatillo than in the tomato varieties in the headspace. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Interestingly, Grape and Campari are two of the smallest varieties of those measured. Results by Xu and Barringer (2010) were similar in that grape tomato had higher levels of volatiles than vine‐ripened, cherry, and roma tomatoes. It was also reported that the formation of a mixture of (Z)‐3‐hexenal and (E)‐2‐hexenal for chewing is greater in cherry tomato than in plum and delice tomatoes (Brauss and others 1998).…”
Section: Resultsmentioning
confidence: 71%
“…Interestingly, Grape and Campari are two of the smallest varieties of those measured. Results by Xu and Barringer (2010) were similar in that grape tomato had higher levels of volatiles than vine‐ripened, cherry, and roma tomatoes. It was also reported that the formation of a mixture of (Z)‐3‐hexenal and (E)‐2‐hexenal for chewing is greater in cherry tomato than in plum and delice tomatoes (Brauss and others 1998).…”
Section: Resultsmentioning
confidence: 71%
“…Methanol, ethanol, acetone, methyl acetate, dimethylsulfide and toluene vapours were selected because they are released from food (meat, 71-74 fruits 28-30,73 and vegetables 73,75 ) and thus can be considered as markers of food deterioration. Methanol, ethanol, acetone, methyl acetate, dimethylsulfide and toluene vapours were selected because they are released from food (meat, 71-74 fruits 28-30,73 and vegetables 73,75 ) and thus can be considered as markers of food deterioration.…”
Section: Ii5 Characterization and Instrumentationmentioning
confidence: 99%
“…The volatile compounds of interest in the headspace of the sample were analyzed by a selected ion flow tube-mass spectrometer (SIFT-MS; VOICE 100, Syft Technologies Ltd., Christchurch, New Zealand) instrument and Syft VOICE-100 software (v.1.4.9.17754, Syft Technologies Ltd., Christchurch, New Zealand) using the method developed by Xu and Barringer (2010). One hundred grams of sample was transferred to a 500 mL glass media bottle with screw top caps and polytetrafluoroethylene-faced silicone septa (Pyrex 1395-45TS, Corning, NY), and placed in a 50C water bath for 60 min prior to the analysis in order to achieve equilibrium of headspace volatiles.…”
Section: Methodsmentioning
confidence: 99%